Digital Data Fostering University Campus Regenerative Design. Issue 2 (3rd July 2022) - Kos, Jose; Miyamoto, James; Mangrich, Camila; Pavan, Luis Henrique
Abstract : Urban Ecology Lab (Laboratorio de Ecologia Urbana—LEUr) Universidade Federal de Santa Catarina (UFSC) Florianópolis, Brasil Universidade Federal do Rio de Janeiro (UFRJ) Rio de Janeiro, Brasil Established: 2012 Leadership: Jose Kos (Founder and Coordinator of LEUr Research Group) James Miyamoto (Coordinator of LEUr-UFRJ) Current Laboratory Structure: Academic Faculty: 6 Research Staff: 1 Postdoctoral Researcher: 1 Graduate Research Assistants: 16 Undergraduate Research Assistants: 15